Efficacy of a platinum-based chemotherapy rechallenge for platinum-sensitive recurrence after PARP inhibitor maintenance - Takehiro Nakao; Kenichi Harano; Masashi Wakabayashi; Yoichi Naito; Hiroshi Tanabe; Toru Mukohara (Elsevier, 2024)
Objective: Platinum-free interval (PFI) is the period from the end of platinum-based chemotherapy to the date of recurrence. If the PFI is > 6 months, a platinum-based chemotherapy rechallenge is considered; however, its efficacy after poly adenosine 5'-diphosphate-ribose polymerase (PARP) inhibitor maintenance therapy is unknown. This study aimed to examine the efficacy of a platinum-based chemotherapy rechallenge after PARP inhibitor therapy. Methods: We retrospectively evaluated patients with ovarian cancer with a PFI≥6 months with PARP inhibitor maintenance therapy, receiving platinum-based chemotherapy. Duration of PARP inhibitor therapy, best response to subsequent platinum chemotherapy rechallenge, and clinical characteristics were collected from medical records. Tumor response was assessed according to RECIST 1.1. Correlations were calculated using Spearman's correlation coefficients. Results: Among the 10 included patients, seven (70 %) received PARP inhibitors after primary chemotherapy, and three (30 %) received chemotherapy for platinum-sensitive relapse. One and five patients harbored a germline BRCA1 and BRCA wild-type mutations, respectively, and two had homologous recombination proficiency. The median PFI was 303.5 (182-602) days, and PARP inhibitor therapy duration was 249 (147-570) days. Platinum chemotherapy rechallenge efficacy was complete and partial response and stable disease in one (10 %), six (60 %), and three (30 %) patients, respectively. The longer the duration of PARP inhibitor treatment, better the response to platinum agents (Spearman correlation coefficient 0.284, p = 0.0288). Conclusion: Platinum-based chemotherapy rechallenge is reasonable for patients with platinum-sensitive disease, using the traditional PFI cutoff of 6 months, even when the PFI is obtained with a maintenance PARP inhibitor.